Design of gas-handling systems and facilities - Stewart, Maurice (Surface Production Operations ;, 2014)
Updated and better than ever, Design of Gas-Handling Systems and Facilities, 3rd Edition includes greatly expanded chapters on gas-liquid separation, gas sweetening, gas liquefaction, and gas dehydration -information necessary and critical to production and process engineers and designers. Natural gas is at the forefront of today''s energy needs, and this book walks you through the equipment and processes used in gas-handling operations, including conditioning and processing, to help you effectively design and manage your gas production facility. Taking a logical approach from theory.